Permeability of canine vocal fold lamina propria. (10th December 2014) - Meyer, Jacob P.; Kvit, Anton A.; Devine, Erin E.; Jiang, Jack
Abstract : Objectives/Hypothesis: Determine the permeability of excised canine vocal fold lamina propria. Study Design: Basic science. Methods: Vocal folds were excised from canine larynges and mounted within a device to measure the flow of 0.9% saline through the tissue over time. The resultant fluid volume displaced over time was then used in a variation of Darcy's law to calculate the permeability of the tissue. Permeability was found through each anatomical plane of the vocal fold, with five samples per plane. Permeability was also found for lamina propria stretched to 10%, 20%, and 30% of its initial length to determine the effects of tensile strain on permeability, with five samples per level of strain. Results: Permeability was found to be 1.40 × 10 −13 m 3 s/kg through the sagittal plane, 1.00 × 10 −13 m 3 s/kg through the coronal plane, and 4.02 × 10 −13 m 3 s/kg through the axial plane. It was significantly greater through the axial plane than both the sagittal ( P = .025) and coronal ( P = .009) planes. Permeability under strain through the sagittal plane was found to be 1.94 × 10 −13 m 3 s/kg under 10% strain, 3.35 × 10 −13 m 3 s/kg under 20% strain, and 4.80 × 10 −13 m 3 s/kg under 30% strain. The permeability significantly increased after 20% strain ( P < .05). Conclusions: Permeability in canine vocal fold lamina propria was found to be increased along the anterior‐posterior axis, following the length of the vocal folds. This may influence fluid distribution within the lamina propria during and after vibration. Similarly, permeability increased after 20% strain was imposed on the lamina propria, and may influence vocal fold dynamics during certain phonation tasks. Level of Evidence: NA Laryngoscope, 125:941–945, 2015